The Implications Of Customary Law Norms In National Criminal Law On Values Of Criminal Justice By Indigenous Peoples - Yohanes Leonardus Ngompat; Dwityas Witarti Rabawati; Finsensius Samara (UNIVERSITAS PAKUAN, 2026)
The reform of criminal law through Law Number 1 of 2023 concerning the Criminal Code is an important step in the decolonization of law in Indonesia while also providing recognition of the laws that exist within society. This recognition is reinforced through Government Regulation Number 55 of 2025 concerning Procedures and Criteria for Determining Laws that Exist within Society. This study aims to analyze and critically examine the normativization of customary law in national criminal law and assess its implications for the values underlying the handling of criminal acts in indigenous communities. This study is a normative legal study using secondary data consisting of primary and secondary legal materials and employing a regulatory and sociological approach to law. The results of the study show that the recognition of living law or customary law in the National Criminal Code reflects efforts to harmonize national law and customary law. However, through Government Regulation No. 55 of 2025, living law or customary law must go through a formalization process, starting from the administrative recognition of customary law communities, the formation of regional regulations, to verification by the central government. This mechanism places the state as the party that determines the validity of customary norms as customary criminal acts. As a result, customary law, which was previously based on material legality, has shifted towards formal legality that depends on state legitimacy. In addition, restrictions on customary criminal acts so as not to conflict with the Criminal Code and the standardization of fines have the potential to reduce the flexibility and character of customary law and open up the possibility of overlapping authority between customary institutions and state law enforcement agencies.